Airborne Microbial Assessment and Its Implication for Laboratory Safety - Hati, Fatmi Indah; Puteri, Siti Noor A’in A’fifah; Khairunnisya, Siti (Poltekkes Kemenkes Tanjung Karang, 2025)
The impact of airborne microbes on laboratory workers is substantial, as exposure to elevated bioaerosol concentrations can lead to respiratory illnesses, allergic sensitization, and an increased risk of laboratory-acquired infections. The air quality in microbiological laboratories is therefore a critical component of occupational health and safety. Previous studies have shown that microbial levels in educational laboratories frequently exceed international and national guidelines. Despite increasing recognition of the importance of indoor air quality, limited data are available on microbiological laboratory conditions outside Java, particularly in South Kalimantan. This study employed a descriptive, cross-sectional, observational design using the midget impinger method to collect air samples at two sampling points in each laboratory before and after ventilation activation, resulting in a total of 12 samples. Airborne bacterial counts were used to quantify microbial load, while temperature and relative humidity were simultaneously measured. Data were analyzed descriptively, and pre–post ventilation differences were assessed using the Wilcoxon Signed-Rank test. All microbial loads remained below the WHO (500CFU/m³) and Ministry of Health Republic Indonesia (700CFU/m³) thresholds. Three laboratories which relied solely on natural ventilation, exhibited the highest microbial counts, whereas laboratories with mechanical ventilation showed consistently lower levels. Although no significant differences were observed between pre-post ventilation conditions, naturally ventilated spaces tended to show higher microbial loads. Overall, airborne microbial levels and environmental parameters across the three laboratories remained within acceptable limits. However, higher humidity was associated with higher microbial concentrations, underscoring the importance of maintaining indoor environmental conditions within recommended ranges to ensure laboratory safety.